Al-Quran Dalam Perspektif Masyarakat Islam Kejawen dan Implikasinya dalam Kehidupan Praksis - Intan Novelia (Fakultas Ushuluddin Adab dan Humaniora (FUAH), Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2019)
This article discusses the Qu’ran from the perspective of the Kejawen Islamic community and its implications in the lives of praxis. This research is a type of field research with the theory of social construction from Peter L. Berger that emphasizes the meaning and a shared-interpretation constructed in community networks. The results showed that the syncretic Kejawen Bonekeling Islamic community had its own views and beliefs about the Qur'an, not as a way of life like Muslims, but as a holy book that would be asked by angels in the grave. This view has implications for their lives. They understand the teachings of Islam in the Qur'an, such as prayer and aurat, different from Muslims in general. Prayer as sembahyang is interpreted as doing good to fellow human beings, getting along well, helping each other to help and protect the traditions of their ancestors. While regarding aurat, they do not have boundaries that must be covered, but they emphasize that the most important thing is to improve themselves first to become a good human being